2023
DOI: 10.1002/fsn3.3218
|View full text |Cite
|
Sign up to set email alerts
|

Combination of the effect of ginger and anti‐inflammatory diet on children with obesity with nonalcoholic fatty liver disease: A randomized clinical trial

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common cause of liver disease in children. Following earlier reports on an increase in the prevalence of childhood obesity, NAFLD is now becoming increasingly common in children. Although no definitive cure exists, early management, early diagnosis, and treatment can reduce its complications. This study aims to determine the effectiveness of the combination of ginger and an anti‐inflammatory diet (AID) in children with obesity on fatty liver management. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…It has been shown that healthy fatty acids (MUFAs and PUFAs [particularly omega‐3 FAs]) could prevent NAFLD by reducing triglycerides, glucose, oxidative stress, and hepatic steatosis as well as improving insulin sensitivity, anti‐inflammatory effect, and inhibiting hepatic fat accumulation (Berge et al, 2014 ; Kamari et al, 2023 ; Spooner & Jump, 2019 ). The main sources of omega‐3 FAs are seafood, seeds, nuts, and plant derivatives (Calder, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that healthy fatty acids (MUFAs and PUFAs [particularly omega‐3 FAs]) could prevent NAFLD by reducing triglycerides, glucose, oxidative stress, and hepatic steatosis as well as improving insulin sensitivity, anti‐inflammatory effect, and inhibiting hepatic fat accumulation (Berge et al, 2014 ; Kamari et al, 2023 ; Spooner & Jump, 2019 ). The main sources of omega‐3 FAs are seafood, seeds, nuts, and plant derivatives (Calder, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Children were divided into four groups: ginger supplement, ginger supplement with the anti-inflammatory diet, control, and antiinflammatory diet alone. Hepatic steatosis, measured via ultrasound and ALT levels, decreased in the ginger and ginger-with-anti-inflammatory-diet groups [48].…”
Section: Antioxidantsmentioning
confidence: 91%
“…One study looked at the effect of 3 g/day on blood lipids in individuals with hyperlipidaemia [136]. Two studies looked at the impact of ginger on liver function, anthropometric measurements, blood sugar and inflammatory markers in individuals with NAFLD [117,123]. One looked at the impact of 1 g of ginger daily in obese children with NAFLD [117], while, in the other study, adults were given 1.5 g/day [123].…”
Section: Gingermentioning
confidence: 99%
“…Two studies looked at the impact of ginger on liver function, anthropometric measurements, blood sugar and inflammatory markers in individuals with NAFLD [117,123]. One looked at the impact of 1 g of ginger daily in obese children with NAFLD [117], while, in the other study, adults were given 1.5 g/day [123]. A pilot study investigated the impact of 1 g/day of ginger on thyroid symptom score, anthropometric measurements, blood glucose and blood lipids in hypothyroid patients [131].…”
Section: Gingermentioning
confidence: 99%